PENGARUH PENGGUNAAN MEDIA DAN METODE PEMBELAJARAN TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR ISLAM TERPADU (SDIT) NURUL IKHLAS BEKASI UTARA - Mohammad Syahid Waliyuddin (Jurnal Riset Multidisiplin Edukasi, 2025)
The main components of motivation are human needs, drives, and goals. Understanding motivation is crucial for all groups, both individuals and society. In education, the role of motivation is crucial, as strengthening motivation can motivate someone to achieve their goals, whether aspirations or learning outcomes. Thus, realizing one's aspirations can encourage them to explore and learn. Conversely, a lack of motivational reinforcement can negatively impact their behavior and learning outcomes.